“Year X of the National Revolution” — Salazarist palingenetic myth in the Diário da Manhã - Joe Williams (Revista Portuguesa de História, 2025)
This paper contributes to the debate surrounding the extent to which Salazarism constituted a fascist ideology by analysing the discourses in an edition of the Diário da Manhã — official organ of the National Union, the only legal political party during the Estado Novo — published on 28 May 1936. This edition of the Diário commemorated 10 years of the May 28 1926 coup which installed the Military Dictatorship, later transformed into the Estado Novo with the 1933 Constitution. This article adopts Roger Griffin’s palingenetic myth analytical framework, which defines fascism in ideal-typological terms with reference to its discursive content, while also incorporating aspects of Emilio Gentile’s notion of the sacralisation of politics, to afford a more nuanced understanding of Salazarism’s ideological foundations. The analysis finds that the discourses in this issue of the Diário exhibit a degree of conformity with Griffin’s definition of a fascist ideology yet with several caveats, concluding that Salazarism can best be described as a para-fascist ideology predicated on a specifically Portuguese configuration of a palingenetic myth rendered via elements borrowed from Catholic discourse to confer Estado Novo politics with sacred dimensions. These findings support the position that Salazarism underwent a degree of fascistisation during the 1930s.